Multiliteracies for a Digital Age - Selber, Stuart A. (Book collections on Project MUSE., 2004)
Just as the majority of books about computer literacy deal more with technological issues than with literacy issues, most computer literacy programs overemphasize technical skills and fail to adequately prepare students for the writing and communications tasks in a technology-driven era. Multiliteracies for a Digital Age serves as a guide for composition teachers to develop effective, full-scale computer literacy programs that are also professionally responsible by emphasizing different kinds of literacies and proposing methods for helping students move among them in strategic ways. Defining.